Pertumbuhan Bibit Stum Mini Tanaman Karet (Hevea brasiliensis Muell Erg) Klon GT 1 Pada Berbagai Media Tanam Dan Pemberian Konsentrasi Rootone-F - Edi Usman Dani; Rustam Baraq Noor; Mahdalena Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2012)
The research aimed to identify the growing of Hevea brasiliensis Muell Erg) Klon GT1 on the Plant Media and Application of Rootone-F Consentration, as well as its interaction, and to find the proper concentration of Rootone-F for Hevea brasiliensis Muell Erg) Klon GT1. The research lasted for four months, from Februari to Mei 2009, at the Village of Loa Bakung Sub District of Samarinda. The research employed Completely Randomized Design with Factorial 4 x 4 and three replications. The first factor was Plant Media (M): top soil (m0); top soil + gambut + sand (2:1:1) (m1); top soil + gambut (3:1) (m2); top soil + sand (3:1) (m3). And the second factor was Rootone-F Consentration (D): no Rootone-F (d0); 2,5 g/litre water (d1); 5 g/litre water (d2); 7,5 g/litre water (d3). Results showed that: (1) significant responses the plant media on the parameters of height plant, number of leaf at the stage of 60 and 90 old days and diameter of stem; (2) significant responses on the application of Rootone-F on the parameters of height plant, number of leaf at the stage of 60 and 90 old days and diameter of stem; (3) there was no significant responses on all parameters upon the interaction between plant media and Rootone-F application.